The potential of digital entrepreneurship in Serbia - Milan Krivokuća; Dragan Ćoćkalo; Mihalj Bakator (Anali Ekonomskog fakulteta u Subotici, 2021)
The development of digital technologies has fundamentally changed all segments of the functioning of human societies and ways of doing business in all activities. Digital entrepreneurship has emerged as a consequence of the development of digital technologies and digitalization. The subject of research conducted in this paper is digital entrepreneurship as a new paradigm of business due to market globalization. The main research problem addressed in this paper is the analysis of the impact that digital entrepreneurship has on business. Within the work, empirical research was conducted, on a sample of 147 respondents, which aimed to point out the potentials that digital entrepreneurship has in the Republic of Serbia. The research conducted in this paper aimed to point out the importance of digital entrepreneurship, as a new business paradigm in globalmarkets, and the potential of digital entrepreneurship in the Republic of Serbia. In addition to a comprehensive analysis of secondary data sources, the results of which are presented in the literature review, the paper also used primary data sources, i.e. the results of research on the potential of digital entrepreneurship in the Republic of Serbia, conducted by the author through an online survey.